Implementasi Supply Chain Management untuk Meningkatkan Kinerja Logistik Perusahaan - Lutfah Nur Anisa; Sifah Andawiah; Dian Putra Utama; Ibnu Afan (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study was to determine the Implementation of Supply Chain Management to Improve the Company's Logistics Performance. Supply Chain Management (SCM) plays an important role in improving the company's logistics performance through technology integration, collaboration with supply chain partners and systematic performance evaluation. This research uses a qualitative approach, this approach is focused and uses a variety of methods, and is carried out naturally and holistically, with an emphasis on quality. The results of the study The implementation of Supply Chain Management integrated with information technology has proven to be able to significantly improve the company's logistics performance. Accelerating the flow of information and collaboration with supply chain partners, the company's logistics, with significant improvements in reliability, cost efficiency, and flexibility, is a key factor in facing dynamic market challenges. However, special attention must be paid to risk management to ensure operational sustainability amid global challenges.